2009
DOI: 10.1161/circulationaha.108.807537
|View full text |Cite
|
Sign up to set email alerts
|

Conventional Dendritic Cells at the Crossroads Between Immunity and Cholesterol Homeostasis in Atherosclerosis

Abstract: Background-Immunoinflammatory mechanisms are implicated in the atherogenic process. The polarization of the immune response and the nature of the immune cells involved, however, are major determinants of the net effect, which may be either proatherogenic or antiatherogenic. Dendritic cells (DCs) are central to the regulation of immunity, the polarization of the immune response, and the induction of tolerance to antigens. The potential role of DCs in atherosclerosis, however, remains to be defined. Methods and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
120
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(127 citation statements)
references
References 40 publications
5
120
1
1
Order By: Relevance
“…On the other hand, DC subsets, including CD11c + CD11b -and CD11b + CD11c + cells, may be pivotal for T cell activation and inflammation during atherosclerosis, similar to their well-defined role in immune responses. Depletion of DCs has also been shown to elevate circulating LDL cholesterol (71). Thus, the observed reduction of lesion size after depletion of APCs in Cd11c-DTR + mice in our study may represent the sum total of all these effects.…”
Section: Discussionsupporting
confidence: 51%
“…On the other hand, DC subsets, including CD11c + CD11b -and CD11b + CD11c + cells, may be pivotal for T cell activation and inflammation during atherosclerosis, similar to their well-defined role in immune responses. Depletion of DCs has also been shown to elevate circulating LDL cholesterol (71). Thus, the observed reduction of lesion size after depletion of APCs in Cd11c-DTR + mice in our study may represent the sum total of all these effects.…”
Section: Discussionsupporting
confidence: 51%
“…on the other hand, Gautier et al (44) found that the expansion of the dc population was not associated with an acceleration of aTS plaque progression in either ldl receptor-deficient or apoE-deficient mice. In these experimental situations, the expansion of the dc population was associated with an atheroprotective decrease in plasma cholesterol levels.…”
Section: Dendritic Cells and Atherogenesismentioning
confidence: 96%
“…The novel in vivo evidence that dcs broadly impact the circulating levels of cholesterol and immune responses in aTS opens new therapeutic horizons in the treatment of aTS (44).…”
Section: Dendritic Cells As Possible Targets In the Treatment Of Athementioning
confidence: 99%
“…Increases in DC populations induced by the overexpression of human Bcl-2 were found to enhance T cell activation and to increase plasma concentrations of Th1-driven IgG2c autoantibodies directed against oxidation specific epitopes, but to decrease plasma cholesterol concentrations (Gautier et al, 2009). …”
Section: Cd68mentioning
confidence: 99%